Preparation method and application of zirconium-erbium co-doped aluminum-based defluorination electrode material

By preparing zirconium-erbium-co-doped aluminum-based fluorine-depleted electrode materials, combined with carbon nanotubes, the problems of low adsorption capacity and poor selectivity of existing electrode materials are solved, and the effects of efficient fluorine removal and low operating costs are achieved.

CN119873981AActive Publication Date: 2025-04-25CHINESE RES ACAD OF ENVIRONMENTAL SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510366229.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-04-25
Estimated Expiration
2045-03-26

AI Technical Summary

Technical Problem

The existing fluorine removal electrode materials have low adsorption capacity and poor selectivity, which leads to high fluorine ion concentration in the effluent water and high operating costs, making it difficult to meet the demand for efficient fluorine removal.

Method used

Using zirconium-erbium-co-doped aluminum-based fluorine-depleted electrode material, ZrO2-ErAlO2/Al2O3 composite material is prepared and mixed with carbon nanotubes (CNTs) to form an efficient electrode material. The material is obtained by ball milling, calcining and grinding of a planetary ball mill, followed by stirring with CNT in an ethanol solution and sonication to form a ZrO2-ErAlO2/Al2O3/CNT powder, and finally prepared into an electrode material by pressing the roller.

Benefits of technology

The fluorine removal efficiency of more than 90% is achieved, the fluorine ion concentration of the effluent water is less than 1 mg/L, which has high selectivity and high processing efficiency, low operating cost, and the performance of the electrode material is reduced after repeated use, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873981A_ABST
    Figure CN119873981A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high-fluorine-content wastewater treatment, relates to a preparation method and application of a zirconium-erbium co-doped aluminum-based defluorination electrode material, and provides a zirconium oxide and erbium oxide co-modified aluminum-based defluorination material, a method for preparing an electrode material through a carbon nanotube and application of the electrode material. The prepared electrode material can achieve the fluorine removal efficiency of 90% or above within 60 min, the concentration of fluorine ions in outlet water is lower than 1 mg / L, the electrode material is not interfered by other anions, and the electrode material has high selectivity and high treatment efficiency and is low in operation cost; in addition, the electrode material can also well realize fluorine ion desorption and regeneration, and has relatively high reutilization performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-fluorine-containing wastewater treatment, and in particular to a preparation method and application of a zirconium-erbium co-doped aluminum-based defluorination electrode material. Background Art

[0002] Fluorine is a trace element necessary for the human body, but long-term excessive intake of high-fluoride water can have serious adverse effects on the gastrointestinal tract, liver, kidneys, nervous system, muscles, reproductive and immune systems, and DNA structure, and even cause bone sclerosis, permanent disability and cancer. In addition to threatening human health, fluorine pollution also has serious harm to the ecological environment. Excessive fluorine content can inhibit soil nitrification and acid phosphatase activity, change the structure and pH of soil protozoan communities, and affect the normal growth of plants.

[0003] The drinking water standard stipulates that the fluoride concentration shall not exceed 1 mg / L. Therefore, in key control areas, the fluoride-containing wastewater generated must be properly treated and can only be discharged after meeting the standards. The treatment methods for fluoride-containing wastewater mainly include chemical precipitation, coagulation precipitation, adsorption and crystallization. In addition, there are membrane separation, ion exchange and electrocoagulation. At present, domestic photovoltaic module manufacturers often use the combination of chemical precipitation and coagulation precipitation to purify water quality by mixing fluoride-containing wastewater from different sources. The most commonly used precipitant in the chemical precipitation method is calcium salt, such as lime, calcium chloride, calcium carbonate and carbide slag. Calcium salt has a good effect on fluoride removal, but the shortcoming in actual engineering is that the calcium fluoride formed by calcium salt and fluorine will be wrapped on the surface of calcium hydroxide, which is not conducive to the complete reaction, resulting in a large amount of calcium salt (the amount added is often 3 to 4 times the theoretical value), high sludge yield and complex composition, low calcium fluoride content, and low reuse value. In addition, the effluent from the chemical precipitation method alone cannot meet the discharge standards. Generally, a coagulant is required for deep defluorination. Commonly used inorganic coagulants are iron salts and aluminum salts, and organic flocculants are mostly polyacrylamide (PAM). The disadvantage of using aluminum salts is that it will introduce aluminum elements that are harmful to the human body and cause excessive chloride ions; and iron salts need to be processed smoothly under higher pH conditions, which will increase the cost of water treatment.

[0004] Capacitor defluorination technology has developed rapidly in recent years. This technology does not require the addition of chemical agents, can avoid secondary pollution, and the electrode materials are reusable. It has the advantages of low long-term operating costs, low energy consumption, and suitability for large-scale applications. Capacitor defluorination technology is suitable for water bodies with different fluoride concentrations, can flexibly respond to a variety of water quality conditions, has high selectivity for fluoride ions, can reduce interference from other ions, and improve treatment effects. However, at this stage, there is still a lack of capacitor defluorination electrode materials with high adsorption capacity, high defluorination efficiency, and high selectivity, which hinders the further development and practical application of this technology.

[0005] Chinese invention patent CN103641201A (publication date: March 19, 2014) discloses a method for preparing a lanthanum-loaded electrode for defluorination electrosorption in drinking water and a defluorination electrode. The composite electrode prepared by the invention has strong defluorination adsorption capacity, high strength, no breakage during long-term use, little mass loss, no dissolution, no secondary pollution problems, and is safe and reliable.

[0006] Chinese invention patent CN107324459A (publication date: November 7, 2017) discloses a method for making a fishbone charcoal defluorination electrode. The main component of the fishbone charcoal in the invention is hydroxyapatite, and it has a porous structure, which can remove fluorine by ion exchange, adsorption, dissolution and precipitation. The fishbone charcoal defluorination electrode can effectively remove fluoride ions at low energy consumption.

[0007] Although the above-mentioned prior art can effectively improve the defluorination efficiency to a certain extent, it does not completely solve the problems of low adsorption capacity, poor selectivity and high effluent concentration existing in the existing defluorination electrodes. Based on this, the present invention provides a preparation method and application of zirconium-erbium co-doped aluminum-based defluorination electrode material to overcome the shortcomings of the prior art. Summary of the invention

[0008] In order to solve the above-mentioned shortcomings of the prior art, the present application provides a method for preparing and applying a zirconium-erbium co-doped aluminum-based defluorination electrode material. The specific technical solution is described as follows.

[0009] A method for preparing a zirconium-erbium co-doped aluminum-based defluorination electrode material comprises the following steps: Step S1: preparing a ZrO2-ErAlO2 / Al2O3 composite material; Step S2: preparing ZrO2-ErAlO2 / Al2O3 / CNT powder; Step S3: preparing electrode materials.

[0010] Furthermore, the step S1 includes the following steps: Step S11: Mix α-Al2O3, Er2O3 and ZrO2 powders and ball mill them in agate medium using a planetary ball mill for 1-2 h; Step S12: calcining the powder mixture obtained in step S11, and grinding it for the second time to eliminate possible agglomerations, to obtain a ZrO2-ErAlO2 / Al2O3 composite material.

[0011] Furthermore, the step S2 is specifically as follows: mixing the ZrO2-ErAlO2 / Al2O3 composite material and CNT in an excess ethanol solution, stirring and ultrasonically treating the mixture, and then drying the ethanol at high temperature to obtain ZrO2-ErAlO2 / Al2O3 / CNT powder; wherein the excess ratio of the ethanol solution to the mixture is 1.5~2.

[0012] Furthermore, in step S11: the mass ratio of the α-Al2O3 and Er2O3 powders is 4-4.5:1, and the mass ratio of the Er2O3 and ZrO2 powders is 1:1-1.5.

[0013] Furthermore, in step S12, the calcination conditions are: temperature of 1200-1500° C. and time of 9-11 hours.

[0014] Furthermore, the mass ratio of the ZrO2-ErAlO2 / Al2O3 composite material to CNT is 1:10-100.

[0015] Furthermore, the stirring time is 2-4 hours, the ultrasonic treatment time is 2-3 hours, and the temperature of drying ethanol is 80-90°C.

[0016] Furthermore, the step S3 specifically includes: pressing the ZrO2-ErAlO2 / Al2O3 / CNT powder obtained in step S2 onto a titanium mesh using a double-roller machine to prepare an electrode material.

[0017] The present invention also provides an aluminum-based defluorination electrode material, which is prepared by the preparation method as described above.

[0018] The present invention also provides an application of the above-mentioned aluminum-based defluorination electrode material in promoting the desorption and regeneration of fluoride ions.

[0019] Compared with the prior art, the advantages and effects of this application are as follows: 1. The present invention provides an aluminum-based defluorination material co-modified with zirconium oxide and erbium oxide, which is prepared into an electrode material through carbon nanotubes. The electrode material can achieve a defluorination efficiency of more than 90% within 60 minutes, has high adsorption capacity and defluorination efficiency, and the fluoride ion concentration of the effluent is lower than 1 mg / L. It is not interfered by other anions, has high selectivity and high treatment efficiency, excellent conductivity, and low operating cost.

[0020] 2. The aluminum-based defluorination electrode material provided by the present invention can achieve good fluoride ion desorption and regeneration, with little performance degradation after repeated use. The surface modification and structure can reduce the adhesion of organic matter or impurities, and has high reuse performance.

[0021] 3. The method for preparing a zirconium-erbium co-doped aluminum-based defluorination electrode material provided by the present invention is environmentally friendly, the required raw materials are easy to obtain, the synthesis process is simple, and it is suitable for large-scale production, taking into account both performance and economy.

[0022] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application so that it can be implemented in accordance with the contents of the specification, and to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the following is a detailed description of the preferred embodiments of the present application in conjunction with the accompanying drawings as follows.

[0023] Based on the detailed description of the specific embodiments of the present application in combination with the accompanying drawings below, those skilled in the art will become more aware of the above and other objects, advantages and features of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For those skilled in the art, other drawings can also be obtained based on these drawings without creative work. In all drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, each element or part is not necessarily drawn according to the actual scale.

[0025] in: Figure 1 It is a microscope image of the crystal structure of ZrO2-ErAlO2 / Al2O3; Figure 2 It is the XRD pattern of the mixture of α-Al2O3, Er2O3 and monoclinic ZrO2 before and after calcination; Figure 3 It is a bar graph of the fluorine removal efficiency of ZrO2-ErAlO2 / Al2O3 at different calcination temperatures; Figure 4 It is a microscope image of ZrO2-ErAlO2 / Al2O3 / CNT powder; Figure 5 It is a bar graph showing the effect of ZrO2-ErAlO2 / Al2O3 and CNT doping ratio on fluorine removal efficiency; Figure 6 It is a line graph of the fluorine removal efficiency of different electrode materials over time; Figure 7 It is a line graph of the effect of different anions on fluoride removal efficiency; Figure 8 It is a schematic diagram of the recycling and regeneration performance of aluminum-based defluorination electrode materials. DETAILED DESCRIPTION

[0026] To make the purpose, technical scheme and advantages of the embodiment of the present application clearer, the technical scheme in the embodiment of the present application will be clearly and completely described below in conjunction with the accompanying drawings in the embodiment of the present application. Obviously, the described embodiment is a part of the embodiment of the present application, rather than all of the embodiments. In the following description, specific details such as specific configuration and components are provided only to help fully understand the embodiments of the present application. Therefore, it should be clear to those skilled in the art that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of the present application. In addition, for clarity and brevity, the description of known functions and structures is omitted in the embodiment.

[0027] It should be understood that the references to "one embodiment" or "this embodiment" throughout the specification mean that the specific features, structures, or characteristics associated with the embodiment are included in at least one embodiment of the present application. Therefore, the references to "one embodiment" or "this embodiment" appearing throughout the specification do not necessarily refer to the same embodiment. In addition, these specific features, structures, or characteristics may be combined in any suitable manner in one or more embodiments.

[0028] In addition, the present application may repeat reference numerals and / or letters in different examples. This repetition is for the purpose of simplicity and clarity, and does not in itself indicate the relationship between the various embodiments and / or settings discussed.

[0029] The term "and / or" in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, B exists alone, and A and B exist at the same time. The term " / and" in this article describes another type of association object relationship, indicating that there can be two relationships. For example, A / and B can mean: A exists alone, and A and B exist alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0030] The term "at least one" in this article is merely a description of the association relationship of associated objects, indicating that there may be three relationships. For example, at least one of A and B can mean: A exists alone, A and B exist at the same time, and B exists alone.

[0031] It should also be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusions.

[0032] Example 1 This embodiment introduces a method for preparing a zirconium-erbium co-doped aluminum-based defluorination electrode material, comprising the following steps: Step S1: preparing a ZrO2-ErAlO2 / Al2O3 composite material; Step S2: preparing ZrO2-ErAlO2 / Al2O3 / CNT powder; Step S3: preparing electrode materials.

[0033] Preferably, the step S1 comprises the following steps: Step S11: Mix α-Al2O3, Er2O3 and ZrO2 powders and ball mill them in agate medium using a planetary ball mill for 1-2 h; Step S12: calcining the powder mixture obtained in step S11, and grinding it for the second time to eliminate possible agglomerations, to obtain a ZrO2-ErAlO2 / Al2O3 composite material.

[0034] Preferably, the step S2 is specifically as follows: mixing the ZrO2-ErAlO2 / Al2O3 composite material and CNT in an excess ethanol solution, stirring and ultrasonically treating the mixture, and then drying the ethanol at high temperature to obtain ZrO2-ErAlO2 / Al2O3 / CNT powder; wherein the excess ratio of the ethanol solution to the mixture is 1.5~2.

[0035] Preferably, in step S11: the mass ratio of the α-Al2O3 and Er2O3 powders is 4-4.5:1, and the mass ratio of the Er2O3 and ZrO2 powders is 1:1-1.5.

[0036] Preferably, in step S12, the calcination conditions are: temperature of 1200-1500° C. and time of 9-11 h.

[0037] Preferably, the mass ratio of the ZrO2-ErAlO2 / Al2O3 composite material to CNT is 1:10-100.

[0038] Preferably, the stirring time is 2-4 hours, the ultrasonic treatment time is 2-3 hours, and the temperature of drying ethanol is 80-90°C.

[0039] Preferably, the step S3 specifically comprises: pressing the ZrO2-ErAlO2 / Al2O3 / CNT powder obtained in step S2 onto a titanium mesh using a double-roller machine to prepare the electrode material.

[0040] The technical effect achieved by this embodiment is: this embodiment provides an aluminum-based fluorine removal material co-modified with zirconium oxide and erbium oxide, which is prepared into an electrode material through carbon nanotubes. The electrode material can achieve a fluorine removal efficiency of more than 90% within 60 minutes, and the fluorine ion concentration of the effluent is lower than 1 mg / L, and is not interfered by other anions, has high selectivity and high treatment efficiency, and has low operating costs.

[0041] Example 2 Based on the above Example 1, this example introduces a method for preparing ZrO2-ErAlO2 / Al2O3 with a specific ratio, comprising the following steps: Step S11: 65.9 mol% of α-Al2O3, 15.5 mol% of Er2O3 and 18.6 mol% of ZrO2 powders are mixed and ball-milled in agate medium using a planetary ball mill for 1 h; wherein the α-Al2O3, Er2O3 and ZrO2 powders are all high-purity commercial powders with a purity of 99.99%; Step S12: calcining the powder mixture obtained in step S11 and grinding it for the second time to eliminate possible agglomeration, thereby obtaining a ZrO2-ErAlO2 / Al2O3 composite material; the crystal structure morphology thereof is shown in the attached Figure 1 , Preferably, in step S12, the calcination conditions are: temperature of 1200-1500°C and time of 10 hours. Figure 2 It can be seen that Er2O3 and monoclinic ZrO2 exist in independent crystal structures before calcination. After calcination, monoclinic ZrO2 is transformed into cubic ZrO2, and Er2O3 and α-Al2O3 form eutectic ErAlO2. Figure 3 It can be seen that the fluorine removal efficiency of ZrO2-ErAlO2 / Al2O3 obtained by calcining at 1400℃ is the highest, that is, 1400℃ is the optimal calcination temperature.

[0042] Example 3 Based on the above-mentioned Examples 1 and 2, this Example further introduces a method for preparing an aluminum-based defluorination electrode material, specifically: ZrO2-ErAlO2 / Al2O3 composite material and CNT are mixed in an excess ethanol solution at a mass ratio of 1:10, 1:20, 1:50 and 1:100, wherein the excess ratio of the ethanol solution to the mixture is 1.5-2, and then after 2 hours of sufficient stirring and 2 hours of ultrasonic treatment, the ethanol is dried at 80°C to obtain ZrO2-ErAlO2 / Al2O3 / CNT powder, the morphology and structure of which can be seen in the attached Figure 4 The ZrO2-ErAlO2 / Al2O3 / CNT powder was pressed onto a titanium mesh using a double-roller machine to prepare an electrode material.

[0043] Please see attached Figure 5 It can be seen that when the mass ratio of ZrO2-ErAlO2 / Al2O3 composite material and CNT is 1:20, the fluorine removal efficiency of the obtained ZrO2-ErAlO2 / Al2O3 / CNT powder is the highest, that is, the optimal mass ratio of ZrO2-ErAlO2 / Al2O3 composite material and CNT when mixed is 1:20.

[0044] Example 4 Based on the above examples 1-3, this example introduces the application of a zirconium-erbium co-doped aluminum-based defluorination electrode material. The electrode material, CNT and ZrO2-ErAlO2 / Al2O3 composite material were used to treat 10 mg / L fluoride-containing wastewater. Figure 6 It can be seen that the electrode material provided in this application can achieve a fluoride removal efficiency of more than 90% within 60 minutes, and the fluoride ion concentration in the effluent is less than 1 mg / L, indicating that it has a high fluoride removal efficiency.

[0045] This example tests the effect of different anions on the defluorination efficiency. Figure 7 . Under the condition of the coexistence of other anions, the electrode material provided by the present application can still achieve a high fluoride removal efficiency, among which the greatest interference comes from HCO3- ions. The fluoride ion concentration of the effluent water increases from 0.51 mg / L to 1.05 mg / L, and the influence of chloride ions and nitrate ions is very small, and the effluent concentration can be maintained below 1.0 mg / L, indicating that the electrode material provided by the present application has good selectivity for fluoride ions and is less affected by other anions.

[0046] Please see attached Figure 8 After a 100-hour continuous defluorination test using the electrode material provided in this embodiment, it was found that the defluorination efficiency was reduced, but still maintained at more than 80%. The resolution rate of fluoride ions during the regeneration process of the electrode material can be maintained at more than 90%, and it has good stability and regeneration ability. This experiment shows that the electrode material provided in this application can achieve good desorption and regeneration of fluoride ions and has good reusability.

[0047] The above description is only the preferred embodiment of the present invention, which does not limit the protection scope of the present invention. For those skilled in the art, the present invention can be modified and varied in various ways. Within the spirit and principle of the present invention, any change, modification, replacement, integration and parameter change of these embodiments by conventional substitution or capable of achieving the same function without departing from the principle and spirit of the present invention shall fall within the protection scope of the present invention.

Claims

1. A method for preparing a zirconium-erbium co-doped aluminum-based defluorination electrode material, characterized in that: The following steps are involved: Step S1: preparing a ZrO2-ErAlO2 / Al2O3 composite material; Step S2: preparing ZrO2-ErAlO2 / Al2O3 / CNT powder; Step S3: preparing electrode materials.

2. The method for preparing a zirconium-erbium co-doped aluminum-based defluorination electrode material according to claim 1, characterized in that: The step S1 comprises the following steps: Step S11: mixing α-Al2O3, Er2O3 and ZrO2 powders and grinding; Step S12: calcining the powder mixture obtained in step S11, and grinding it for the second time to obtain a ZrO2-ErAlO2 / Al2O3 composite material.

3. The method for preparing a zirconium-erbium co-doped aluminum-based defluorination electrode material according to claim 1 or 2, characterized in that: The step S2 is specifically as follows: mixing the ZrO2-ErAlO2 / Al2O3 composite material and CNT in an excess ethanol solution, stirring and ultrasonically treating, and then drying the ethanol at high temperature to obtain ZrO2-ErAlO2 / Al2O3 / CNT powder; wherein the excess ratio of the ethanol solution to the mixture is 1.5-2.

4. The method for preparing a zirconium-erbium co-doped aluminum-based defluorination electrode material according to claim 2, characterized in that: In step S11: the mass ratio of the α-Al2O3 and Er2O3 powders is 4-4.5:1, and the mass ratio of the Er2O3 and ZrO2 powders is 1:1-1.

5.

5. The method for preparing a zirconium-erbium co-doped aluminum-based defluorination electrode material according to claim 2 or 4, characterized in that: In step S12, the calcination conditions are: temperature of 1200-1500° C. and time of 9-11 hours.

6. The method for preparing a zirconium-erbium co-doped aluminum-based defluorination electrode material according to claim 3, characterized in that: The mass ratio of the ZrO2-ErAlO2 / Al2O3 composite material to CNT is 1:10-100.

7. The method for preparing a zirconium-erbium co-doped aluminum-based defluorination electrode material according to claim 3, characterized in that: The stirring time is 2-4 hours, the ultrasonic treatment time is 2-3 hours, and the temperature of drying ethanol is 80-90°C.

8. The method for preparing a zirconium-erbium co-doped aluminum-based defluorination electrode material according to claim 1, 2 or 4, characterized in that: The step S3 specifically comprises: pressing the ZrO2-ErAlO2 / Al2O3 / CNT powder obtained in the step S2 onto a titanium mesh to prepare an electrode material.

9. An aluminum-based defluorination electrode material, characterized in that: The material is prepared by the method for preparing a zirconium-erbium co-doped aluminum-based defluorination electrode material as described in any one of claims 1 to 8.

10. Use of an aluminum-based defluorination electrode material according to claim 9 in promoting the desorption and regeneration of fluoride ions.

Citation Information

Patent Citations

  • Novel polymer-based composite material and preparation method of composite material as well as method for deep fluorine removal of water body

    CN102942239A

  • Making method of fish bone charcoal fluoride removal electrode

    CN107324459A

  • Polyaniline modified aluminum oxide ceramic membrane and electro-adsorption defluorination method thereof

    CN113368709A

  • Method of making an electrode for electrolysis cells and an electrode produced thereby

    GB1437920A

  • Positive electrode for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

    US20150132666A1